2009
DOI: 10.5194/hess-13-833-2009
|View full text |Cite
|
Sign up to set email alerts
|

EAGLE 2006 – Multi-purpose, multi-angle and multi-sensor in-situ and airborne campaigns over grassland and forest

Abstract: Abstract. EAGLE2006 -an intensive field campaign for the advances in land surface hydrometeorological processes -was carried out in the Netherlands from 8th to 18th June 2006, involving 16 institutions with in total 67 people from 16 different countries. In addition to the acquisition of multiangle and multi-sensor satellite data, several airborne instruments -an optical imaging sensor, an imaging microwave radiometer, and a flux airplane -were deployed and extensive Correspondence to: Z. Su (b su@itc.nl) grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 12 publications
(5 reference statements)
1
50
0
Order By: Relevance
“…Ezzahar et al (2007) have suggested that the differences between the two measurements could be explained by differences in terms of the source areas of the LAS and EC and the closure failure of the energy balance of the EC. Su et al (2009) have proposed that the difference between the two measurements may be attributed to the sensitivity of the H LAS to the aerodynamic roughness length Fig. 9, which reveals that the H EC and H LAS were much closer to each other, with only a 6% difference (R 2 = 0.67, n = 1202).…”
Section: Comparison Of the Sensible Heat Fluxes Derived From Las And Ecmentioning
confidence: 98%
“…Ezzahar et al (2007) have suggested that the differences between the two measurements could be explained by differences in terms of the source areas of the LAS and EC and the closure failure of the energy balance of the EC. Su et al (2009) have proposed that the difference between the two measurements may be attributed to the sensitivity of the H LAS to the aerodynamic roughness length Fig. 9, which reveals that the H EC and H LAS were much closer to each other, with only a 6% difference (R 2 = 0.67, n = 1202).…”
Section: Comparison Of the Sensible Heat Fluxes Derived From Las And Ecmentioning
confidence: 98%
“…In addition, several airborne campaigns were performed to assess SSM retrieval over large areas: EuroSTARRS in France and Spain (Saleh et al, 2004), NAFE/CoSMOS in Australia (Panciera et al, 2008), EA-GLE2006 in Germany (Su et al, 2009), HOBE in Denmark (Bircher et al, 2012). These studies showed that the response of L-band brightness temperatures to SSM is affected by biomass conditions (Saleh et al, 2004).…”
mentioning
confidence: 99%
“…The surrounding area is characterized by the presence of broadleaved and coniferous tree species, distributed in blocks around the tower site (Bosveld and Bouten, 2001). Within a 500 m radius it is possible to find native tree species such as beech (Fagus sylvatica L.), pedunculate oak (Quercus robur L.) and Scots pine (Pinus sylvestris L.), as well as the introduced species hemlock (Tsuga heterophylla (Rafinesque) Sargent) and Japanese larch (Larix kaempferi (Lambert) Carriére) (Erisman et al, 1998;Raj et al, 2014;Su et al, 2009;Bosveld and Bouten, 2001;Tietema et al, 2002;Van Wijk et al, 2000;Weligepolage et al, 2013). Canopy heights differ between cover types depending on species and growing stage.…”
Section: Study Sitementioning
confidence: 99%